Synthesis of polycationic bentonite-ionene complexes and their benzene adsorption capacity - Campos, Valquiria [UNESP]; Tcacenco, Celize Maia (Assoc Brasil Polimeros, 2015)
The purpose of this work was to structurally modify clays in order to incorporate water-insoluble molecules, such as petroleum hydrocarbons. The potential for ion exchange of quaternary ammonium salts was studied, which revealed their ability to interact with anions on the cationic surface, for environmental applications of the material. Ionenes, also known as polycations, have many potential uses in environmental applications. In this work, cationic aliphatic ammonium polyionenes, specifically 3,6-ionene and 3,6-dodecylionene, were prepared for incorporation into clay to form bentonite-ionene complexes. The intercalation of bentonite with ionene polymers resulted in an increase in the basal spacing of 3,6-dodecylionene from 1.5-3.5 nm. The higher d001 spacing of 3,6-dodecylionene samples than that of 3,6-ionene samples may be attributed to their longer tail length. The behavior of the TG/DTG curves and the activation energy values suggest that 3,6-dodecylionene (E = 174.85 kJ mol(-1)) is thermally more stable than 3,6 ionene (E = 115.52 kJ mol(-1)) complexes. The adsorption of benzene by 3,6-ionene and 3,6-dodecylionene was also investigated. The increase in benzene concentrations resulted in increased benzene adsorption by the sorbents tested in this work. The sorption capacity of benzene on ionene-modified bentonite was in the order of 3,6-dodecylionene > 3,6-ionene.
Keywords: 3,6-ionene; 3,6-dodecylionene; Synthesis; Adsorption of benzene